Ethnopharmacological study on traditional medicinal plants of the anak dalam tribe in Bukit Dua Belas, Jambi Province as a treatment for diarrhea and antibacterial test - Yolandari, Febby Ola; Djamil, Ratna; Chaidir, Chaidir (Institute of Computer Science (IOCS), 2025)
The Anak Dalam Tribe or Orang Rimba is one of the tribes that live on the island of Sumatra, precisely located in Jambi Province. The Anak Dalam Tribe utilizes plants as a necessity in their lives, one of the benefits of plants used by the Anak Dalam Tribe community as a cure for a disease. This study aims to examine the potential of plants as a cure for diarrhea in the Anak Dalam Tribe, Bukit Dua Belas. This type of research is descriptive research with qualitative methods and snowball sampling techniques through open-ended interviews with 5 informants as Temenggung or tribal chiefs, and 1 informant who is a shaman using interview guidelines. Based on the results of the interview, 14 types of single plants and 4 types of plants in the form of potions were obtained which were used as diarrhea medicine. The plant organs that are utilized include roots, leaves, sap, mushrooms, tubers. The processing method is boiled, squeezed, burned, grated. While its use is by eating, drinking and, sticking to the part of the body that is sick. In the treatment process in the Anak Dalam Tribe, Bukit Dua Belas still uses spiritual methods by relying on the help of Dewo or supernatural powers. In the bacterial inhibition test, the average clear zone results were wider than the others in the test with 96% ethanol extract with Escherichia coli bacteria, the widest clear zone was found in the Lelisau plant at 14.1 mm, in Staphylococcus aureus bacteria, the widest clear zone was in the Mempalas plant at 10.7 mm so that it was included in the strong category. Testing the diameter of the inhibition power using water extract tested with Escherichia coli bacteria, the widest clear zone was found in the Lelisau leaves at 12.35 mm, in Staphylococcus aureus bacteria, the widest clear zone was in the Water Apple plant at 10.6 mm so that it was included in the strong category.